Doctoral Dissertations by University of The Bahamas Faculty or About The Bahamas, 2012 - 2019 - Munroe-Whylly, Rosemary; Hinsey, Shananda M. (International Journal of Bahamian Studies, 2020)
The purpose of this bibliography is to highlight the dissertations that support the achievement of doctoral degrees of the faculty of the University of the Bahamas, formerly The College of The Bahamas, as well as doctoral research about the Bahamas produced from 2012-2019. This compilation continues the previous bibliographies compiled by Dr. Berthamae Walker in 2003, 2005, 2008 and 2012. The entries for 2012 included in this bibliography are the omissions from the previous article published.